Pengamanan Pesan Menggunakan Metode MLSB PRNG dan Kompresi File dengan Algoritma RLE pada File Audio - Rivaldo, Rian; Handrizal, Handrizal; Herriyance, Herriyance (Universitas Diponegoro, 2021)
The development of sending messages from one place to another can be done regardless of distance and time. However, the delivery of these messages is hampered by problems of confidentiality and message security. Especially if the data contains important and confidential information that not just anyone is allowed to read and find out about it. In overcoming this problem, steganography techniques can be used with the Modified Least Significant Bit algorithm, where the determination of the embedding index is based on random numbers generated by the Pseudo-Random Number Generator with the Multiply with Carry algorithm. In addition to security, data size is also an important factor in data transmission. The larger the size the more time it will take to transmit the data. Therefore, the Run Length Encoding algorithm is needed to compress the data size, which will shorten the time to transmit the data. In the message extraction process, a stego key is needed to generate random numbers. Based on the testing of the extraction process with an arbitrary key, it is obtained that the message tested is not the original message that has been embedded previously. In the results of the embedding and extraction process, it is obtained that the average value of PSNR is 63.61498 dB, which means the quality of the stego object produced is quite good. Whereas the measurement of file compression performance results with an average value of Compression Ratio at 1.00113, Space Savings at 0.1133%, and Bitrate at 584025.33 bits/sample. These results indicate that RLE algorithm compression is not efficient to compress file sizes.